Karakteristik Peserta Didik Perspektif Imam Ibnu Jamaʿah: Studi Kitab Tadzkirah Al-Sāmiʿ wa al-Mutakallim fī al-ʾAdab Al-ʿĀlim wa Mutaʿallim karya Imam Badruddin Ibnu Jamāʿah - Maryono Maryono (STAI Ali bin Abi Thalib Surabaya, 2020)
Students who are objects in the educational process are the main pillars in achieving educational goals. In this paper describes the